The Canadian Statistical Sciences Institute 2003–2022. Issue 4 (4th July 2022) - Thompson, Mary; Reid, Nancy; Estep, Don
Abstract: This article describes the founding and growth of the Canadian Statistical Sciences Institute (CANSSI), starting from its early roots and continuing through to establishment as a mature research enterprise. The goal is to present a historical record of events and activities that were important in the development of CANSSI. Résumé: Cet article décrit la création et le développement de l'Institut canadien des sciences statistiques (INCASS), depuis ses débuts jusqu'à son établissement en tant qu'entreprise de recherche mature. L'objectif est de présenter un historique des événements et des activités qui ont été importants dans le développement de l'INCASS.